2011
DOI: 10.1186/1742-2094-8-139
|View full text |Cite
|
Sign up to set email alerts
|

Brain microvascular pericytes are immunoactive in culture: cytokine, chemokine, nitric oxide, and LRP-1 expression in response to lipopolysaccharide

Abstract: BackgroundBrain microvascular pericytes are important constituents of the neurovascular unit. These cells are physically the closest cells to the microvascular endothelial cells in brain capillaries. They significantly contribute to the induction and maintenance of the barrier functions of the blood-brain barrier. However, very little is known about their immune activities or their roles in neuroinflammation. Here, we focused on the immunological profile of brain pericytes in culture in the quiescent and immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
155
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 189 publications
(162 citation statements)
references
References 46 publications
5
155
1
1
Order By: Relevance
“…At the protein level, we have corroborated the secretion of CXCL1, CXCL2, CXCL3, CCL2, IL-6, and IL-8 by LPS and HMGB1-stimulated pericytes. Interestingly, when compared with previous results using LPS-treated mouse brain pericytes (16), the profile of cytokines and chemokines released by HBVPs is considerably different. Stimulation of mouse brain pericytes with LPS at the same concentration used in this study resulted in significant release of IL-1␣, TNF-␣, IL-3, IL-10, IL-12 (p70), IL-13, G-CSF, GM-CSF, and CCL5, which were undetectable in the conditioned medium of stimulated HBVPs.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…At the protein level, we have corroborated the secretion of CXCL1, CXCL2, CXCL3, CCL2, IL-6, and IL-8 by LPS and HMGB1-stimulated pericytes. Interestingly, when compared with previous results using LPS-treated mouse brain pericytes (16), the profile of cytokines and chemokines released by HBVPs is considerably different. Stimulation of mouse brain pericytes with LPS at the same concentration used in this study resulted in significant release of IL-1␣, TNF-␣, IL-3, IL-10, IL-12 (p70), IL-13, G-CSF, GM-CSF, and CCL5, which were undetectable in the conditioned medium of stimulated HBVPs.…”
Section: Discussionmentioning
confidence: 76%
“…In a series of pioneering works by Edelman et al (13)(14)(15), the authors demonstrated the expression of TLR4 by Western blotting in rat lung pericytes (13) as well as increased vessel permeability (14) and production of IL-1␤ (15) in LPS-treated pericytes, suggesting for the first time an active role of pericytes in the inflammatory cascade. More recently, the release of nitric oxide and several cytokines and chemokines by mouse brain vascular pericytes in response to LPS has been reported (16). Other interesting works studied the expression of immunologically relevant cell surface proteins by human pericytes after stimulation with TNF-␣ or IFN-␥ (17, 18) but not with LPS.…”
mentioning
confidence: 99%
“…In contrast to the numerous studies assessing the crosstalk among brain endothelial cells, astrocytes and microglia during inflammation, little is known about the role played by the brain microvascular pericyte. In fact, the response of brain pericytes to pro‐inflammatory stimuli has only been addressed in the last few years 2, 3, 4. In a pioneering work, Kovac et al .…”
Section: Introductionmentioning
confidence: 99%
“…The BBB endothelial cells respond to inflammatory stimuli such as cytokines, 186 LPS, 187,188 Ab, [189][190][191] and a truncated tau fragment 192 by activating signaling pathways that result in the upregulation of proinflammatory second messengers and reactive oxygen/ nitrogen species, ultimately causing BBB disruption and paracrine activation of surrounding cells that are responsive to such stimuli, such as astrocytes 193 and pericytes 153,194 of the NVU. Inflammation impairs systemic clearance of Ab by the liver and kidneys, as well as bulk flow of CSF.…”
Section: Alzheimer's Disease Risk Factors and The Blood-brain Barriermentioning
confidence: 99%
“…123,151 Whether pericytes have a similar Ab clearing function is presently unknown, but they do express LRP-1. 152,153 The Astrocytes Astrocytes are the most abundant cell type in the brain, and have important functions in the BBB. Their endfeet surround the endothelium of capillaries, arterioles, and venules.…”
mentioning
confidence: 99%